Civic Education in the UK and Japan - Ayhan Azan (CV Tirta Pustaka Press, 2024)
Every country has a unique civic education system in accordance with its values, history, and system of government. Several countries worldwide, including the UK and Japan, need to focus on implementing civic education. The approach used in writing this article is a qualitative approach with a literature review method. Civic education in the UK should be an education to build civic identity, with the center of attention on three “strands” of work, namely “social and moral responsibility, community involvement, and political literacy”—or” the development of social and moral responsibility, community involvement, and political literacy. Civic education in Japan, known in the terminology of social studies as living experience and moral education, is oriented towards the experiences, knowledge, and abilities of citizens in relation to efforts to build the Japanese nation.Thus, it can be concluded that this paper mainly focuses on examining the birth context, development foundation, systemic framework, curriculum, and teaching materials of civic education in Japan.